Unmanned aerial vehicles (UAV) as a support to visual inspections of concrete dams - Henriques, M. J. (2015)
Drone or UAV (unmanned aerial vehicle) are the most common names used to refer light aircrafts without human pilots aboard. This paper presents one application that explores its use as a carrier of digital cameras, allowing the acquisition of images at distances of a few meters of a dam. Dams, and especially large dams, are structures that usually present high risk. For this reason they are subject to surveillance to evaluate its safety. Visual inspections contribute to the knowledge of the structure and are irreplaceable since some problems can only be detected, and their evolution followed, by this method. If to make a photographic reportage inside galleries or in other accessible areas is easy, when one must evaluate the state of the exterior walls or other inaccessible locations on dams, the only method available to inspect the surface was to set the camera/binoculars on the banks of the river. Drones can easily overcome this problem, since they can be guided near the structure, at distances of a few meters This paper presents the results of an experience made at Bouçã dam: it is described the UAV system used, the dam, the flights, the photogrammetric products generated (orthomosaic and point cloud), the problems faced. In Figures 1 and 2 are presented two photographs of Bouçã dam taken during this experiment by a digital camera carried by a drone octocopter.